AKIBAT HUKUM PERATIFIKASIAN PERJANJIAN INTERNASIONAL DI INDONESIA: STUDI KASUS KONVENSI PALERMO 2000 - Dewanto, Wisnu Aryo (Faculty of Law, Parahyangan Catholic University, 2015)
AbstractRatification in Indonesia does not have any legal consequences for the application of the treaties at national level. The reason is that ratification only binds Indonesia as a subject of international law. In comparison, parliamentary approval in the Indonesian context is not the same as the United States Senate’s approval. The Indonesian Government signed the Palermo Convention on December 12, 2000 and ratified it on April 20, 2009. The issue discussed here regards the legal status of this Convention. In the 80’s it was assumed that any treaties ratified or acceded, would ipso facto be enforceable in Indonesia. I argued that Indonesia should be regarded as a state applying the monist approach, which legal practice seems to reject. I stand for the monist approach especially with regard to the legal status of the 2000 Palermo Convention. In addition I also argue about the importance of differentiating between Indonesia’s international obligations and the issue of direct applicaton of the Convention by national couts. Keywords: Ratification, Integration, Implementation, Treaty, Indonesia’s legal system